The Effect of Psychological Capital on Organizational Citizenship Behavior with Work Engagement as a Mediating Variable in Millennial Generation Employees at Bandung City Startups - Anisya Nurfitri Kustyani; Hilmiana Yudomartono; Imas Soemaryani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The problem studied in this study is that employees at startups are required to work extra and voluntarily work beyond their targets for the sustainability of the startup business, but this is suspected by the low organizational citizenship behavior of millennial generation employees in startup Bandung. This study aims to find out how the influence of psychological capital on organizational citizenship behavior through work engagement to millennial generation employees in Bandung city startups. The sample in this study used convenience sampling with the results of a sample calculation of 220 respondents. The questionnaire was used as a data collection technique in this study and was studied with a verifiable and descriptive method, using the SEM data analysis design and the analysis tool used, namely IBM SPSS AMOS 24. The results showed that there is no significant influence between psychological capital variables directly on organizational citizenship behavior. Furthermore, related to the findings of psychological capital, it has a positive and significant effect on work engagement, and work engagement has a significant and positive influence on organizational citizenship behavior. In this study, engagement shown to mediate the influence of psychological capital on organizational citizenship behavior positively and significantly.